PRENATAL GENTLE YOGA HELPS PREGNANT WOMEN IN REDUCING FEAR OF CHILDBIRTH - Astuti, Yunita Laila; Chou, Hsueh Fen; Liu, Chieh Yu; Kao, Chien Huei (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2023)
Background: Expectant mothers will experience physiological and psychological changes during pregnancy, including feeling fear of childbirth.  Fear is a psychological condition that can raise catecholamine levels and decrease uterine contractions, slowing down the labor process. Prenatal exercise such as Prenatal Gentle Yoga is developed to increase healthy pregnancy that may reduce fear of childbirth. This study aimed to evaluate the effect of Prenatal Gentle Yoga on fear of childbirth in pregnant women.Methods: This research used a cross-sectional case-control study, conducted from July to August 2018 in Central Java Province. This study involved 130 first-time expectant mothers. A demographic questionnaire and the Wijma Delivery Expectancy/Experience Questionnaire version A were used for data collection. Cross-tabulation and chi-square was used to analyse the demographic information. Independent samples t-test and one-way ANOVA were used to determine the differences in W-DEQ scores between the two groups. This study also used hierarchical multiple linear regression to determine predictors of fear of childbirth.Results:Three variables significantly impacted fear of childbirth were education level, number of ultrasound examinations, and participation in Prenatal Gentle Yoga classes. Prenatal Gentle Yoga reduced fear of childbirth among participants who attended eight hours or more of classes compared to those who did not (p<.001). Participation in Prenatal Gentle Yoga was the only factor that strongly predicted childbirth fear (R2=.26).Conclusions: This study concluded that Prenatal Gentle Yoga can decrease childbirth fear. Thus, Prenatal Gentle Yoga is recommended for pregnant women in order to reduce fear of childbirth.